PENGARUH STORYTELLING MARKETING TERHADAP BRAND EQUITY DAN KEPUTUSAN PEMBELIAN (Survei Pada Video Iklan Allure Matcha Latte Story Di Youtube) - Nirakatriena Pravitaswari; Zainul Arifin; M. Kholid Mawardi (Fakultas Ilmu Administrasi Universitas Brawijaya, 2018)
This study aims to examine the effect of Storytelling Marketing on Brand Equity and its impact on Purchase Decision. The survey was conducted on 100 active netizens who had purchased and consumed Allure Matcha Latte products, besides having an email account so they could watch, comment on the ALLURE Matcha Latte video ad in the form of a short story entitled